Analisis Fungsi Implikatur Wacana Pojok Mang Usil sebagai Sarana Sindiran dan Kritik Menjelang Pemilu - Novalia, Maulida Rizka; Junawaroh, Siti; Resticka, Gita Anggria (Faculty of Humanities, Diponegoro University, 2024)
There have been quite a lot of studies on the Samin community with various approaches. This research aims to explain the symbolic meaning and essence of Samin's teachings/stitutors using the concept of signs as stated by Saussure and semantics as explained by Pateda using the literature study method. The data was processed using steps as offered by Miles Haberman: data reduction, data recording, and inference. The results of this research are (1) Samin's teachings contained in angger-angger (pratikel, pangucap, and lakonana) are still being maintained, (2) social changes have begun to be discovered, (3) using ngoko language in every domain, (4) symbolic meaning of the three anggers: do good to others, do not indulge in lust, be honest, one word with deeds, pay attention to property rights; (because) the essence of life is one, forever, and death is essentially just